A Suggested Model For Using Customer’s Data Management Information System/ A Case Study In Al-Rasheed Bank/General Agent Office/ Nothren Reigon - زينل بشرى علي (Journal of Economics and Administrative Sciences, 2017)
This study aim to identify the concept of web based information systems since its one of the important topics that is usually omitted by our organizations, in addition to, designing a web based information system in order to manage the customers data of Al- Rasheed bank, as a unified information system that is specialized to the banking deals of the customers with the bank, and providing a suggested model to apply the virtual private network as a tool that is to protect the transmitted data through the web based information system. This study is considered important because it deals with one of the vital topics nowadays, namely: how to make it possible to use a distributed information systems based on the web without having sufficient infrastructure. To achieve the goals of the study we designed a web based information system by using a high level programming language (PHP), and linking it to My SQL language to build a database for the system, and we chose Al-Rasheed Bank/ general agent office/ northern region as the study’s scope and excute the research, We can summarize the research problem with the following research questions:Does Al-Rasheed Bank/ General Agent Office/ Northern Region have enough infrastructure components to excute a distributed information system for managing customer’s data in the real world?, Does the bank have a unified system that combines the bank’s branches and then connecting it with the central bank in Baghdad.?, Does the system that have been used in every branch in the bank satisfy all customer’s requirments which include speed, security, accuracy, and avoiding human errors. And the study ended with a set of conclusions, the most important ones are that the web based information system represents a new generation of information systems which is based on the exploitation of the internet that connects the whole world, and thus reduces the need of the time, effort and the money made to link and organize the information and the private businesses of the organizations in the geographical spread wide, and representing a suggested customers data management system reduces the redundancy problem in customers data, and unifies the information of the different departments of the bank. Based on the conclusions the study ended with a set of suggestions, the most important ones are unifying the work of all the departments of the bank, and the line of its work, which is make it easy to assure the existence of previous information about the customers, or previous accounts of the customers in any of the departments of the bank.